Education for Sustainability: A Snakes and Ladders Game? (Foro de Educacion, 2015)
Over twenty years after the 1992 Rio Summit, no nation has yet made significant advances towards sustainable development. The State of the World reports produced annually by the WorldWatch Institute document the lack lustre agreements form international conferences that have failed to commit governments to meaningful climate change legislation, have been unable to address poverty where it matters most or enact change that would halt the systematic efforts that exploit people and planet. Read More. . .